Alokasi waktu gender dalam aktivitas rumah tangga nelayan pembudidaya tambak Udang Vaname di Desa Towua Kecamatan Wundulako Kabupaten Kolaka - Yosan; Sarinah; Riani, Irdam; Rosmawati; Patiung, Seventry Meliana (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims to determine the allocation of gender time in the households of fisherman cultivating vannamei shrimp ponds in Towua Village, Wundulako District, Kolaka Regency in productive, reproductive and social activities during the periode of November 20021. The population in this study, total 41 household. The sampling method was carried out using a simple random sampling technique, the number of samples selected was 14 vannamei shrimp farming households. Because this research is in a gender perspective, those who will be interviewed are men and women, in this case husbands and wives in every fishing household for vannamei shrimp ponds. Data obtained through observation, interviews and documentation. The data used are primary and secondary data. The method used is descriptive analysis using the Harvard Analitical Framework (HAF) in the households of fishermen culttivating vannamei didl shrimp pond, towua village wundulako subdistrict, it can be seen that there are real differences in the allocation of time used in the division of labor between husband and wife in produtive, reproductive and social activities for productive activities, husbands are more dominant than wives, husbands have working houurs of 5757.80 hours/3 monts with a percentage of 53.62%, while in reproductive and social activities wives have working hours of 1042.130 hours/3 months with a percentange 53.62% while in social activities the wife has worked 26.93 hours/3 months with an achievement of 1.39% method, by looking at how much income the fishing households cultivate in vaname shrimp ponds. The highest household income obtained from the cultivation of vaname shrimp ponds was Rp Rp67,200,000/cycle, the lowest was Rp67,200,000/ cycle and the average household income obtained was Rp25,856,933/ cycle.